Study on the optimization algorithm of the cross-sectional layout of an umbilical based on the layering strategy. (15th July 2021) - Yang, Zhixun; Yin, Xu; Yan, Jun; Shi, Dongyan; Lu, Qingzhen; Wang, Lifu
Abstract: As a key device in subsea production system of the offshore hydrocarbon resources exploitation, the umbilical consists of a variety of functional components such as hydraulic tubes, electrical cables and optical cables. The cross-sectional layout design plays an important role in the performance of an umbilical. Considering the mechanical and geometrical properties as the quantitative design objectives, the mathematical model of multi-objective optimization of the cross-sectional layout of an umbilical is described. Meanwhile, the algorithm of smallest radius of the enclosing circle and the multiplier penalty function method are proposed. Then, the manufacture factor is considered and the layering strategy based on the identification of contact points is introduced to modify implement algorithm to obtain the optimal cross-sectional layout with layering characteristic. Finally, some case studies are performed, the optimal cross-sectional layouts with layering characteristic are obtained. Comparing with the initial design and cross-sectional layouts without layering, the results verify the feasibility of the presented optimization design algorithm, which can improve the design efficiency of an umbilical and avoid the manual process. Highlights: The cross-sectional layout design of the umbilical is often difficult to achieve the rapid optimization design. The quantifiable multi-objective optimization model for the cross-sectional layout of the umbilical is proposed. The multiplier penalty function optimization algorithm is introduced to copy with the optimization model. The layering strategy is introduced to obtain the optimal cross-sectional layout with layering characteristic. The proposed optimization design algorithm can improve the design efficiency of an umbilical and avoid the manual process.